PENGARUH SUHU PENYIMPANAN DAN WAKTU FERMENTASI TERHADAP KUALITAS CUKA APEL MANALAGI - Zuhdi Ma’sum (Universitas Tribhuwana Tunggadewi, 2006)
One of the methods to increase the efficiency of farming product is to the product to become durable product, for example, apple is processed to become vinegar through fermentation. The purpose of this research was to find out whether or not apple fermentation process can produce alcohol with khamir sacharomyces cereviceae, and further fermentation can form vinegar with acetobacter aceti bacteria. In addition, the special purpose of this study was to know the influence of the storage temperature and the fermentation process time on the quality of vinegar production. The results of this research hopefully could increase knowledge about apple processing to become acetic acid. Thus as the constant variable was volume of apple essence, the amount of ammonium sulfate, khamir, acetobacter aceti, time of storage, pH speed of stirrer and temperature of fermentation, where as change of variable was process time. From the research results it was known that the best quality of acetic acid was obteianed at the 62nd hour in the amount of 0.91% (room temperature) and 0.54667% (freezer temperature)